2023
DOI: 10.1007/s00277-023-05393-1
|View full text |Cite
|
Sign up to set email alerts
|

Outcome prediction by interim positron emission tomography and IgM monoclonal gammopathy in diffuse large B-cell lymphoma

Abstract: In diffuse large B-cell lymphoma (DLBCL), a positive interim positron emission tomography (PET) scan predicts treatment failure, but the proportion of high-risk patients thus identified is small. To improve prediction, we combined the interim PET result with the presence or absence of an associated IgM gammopathy. Of 108 DLBCL patients participating in a prospective trial, nine (8%) were interim PET positive and 19 (18%) had an IgM gammopathy. The monoclonal protein was not associated with distinguishing genet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…In DLBCL, only the IgM PP has been reported, by almost all authors from the western world, to be a strong prognostic factor, independent from the IPI score, for both PFS and OS [ 33 , 34 , 35 , 36 , 38 ] Noteworthy, Cox et al, reported the detection of recurrent mutations in high impact genes, and the preferential IGVH4-34 gene usage, which allowed them to hypothesize that most IgMs-DLBCL originate from immune-escaped autoreactive B-cells [ 36 ]. Indeed, this feature [ 59 ] may also explain the high rate of CNS spreading [ 35 , 36 , 38 ]. Conversely, Johansson et al [ 38 ] found no prevalence of specific gene mutations and of the ABC-type.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In DLBCL, only the IgM PP has been reported, by almost all authors from the western world, to be a strong prognostic factor, independent from the IPI score, for both PFS and OS [ 33 , 34 , 35 , 36 , 38 ] Noteworthy, Cox et al, reported the detection of recurrent mutations in high impact genes, and the preferential IGVH4-34 gene usage, which allowed them to hypothesize that most IgMs-DLBCL originate from immune-escaped autoreactive B-cells [ 36 ]. Indeed, this feature [ 59 ] may also explain the high rate of CNS spreading [ 35 , 36 , 38 ]. Conversely, Johansson et al [ 38 ] found no prevalence of specific gene mutations and of the ABC-type.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, this feature [ 59 ] may also explain the high rate of CNS spreading [ 35 , 36 , 38 ]. Conversely, Johansson et al [ 38 ] found no prevalence of specific gene mutations and of the ABC-type. Therefore, more studies are necessary to shed light on the molecular correlatives and the etiopathogenesis of the IgMs-DLBCL subset.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations